The reliability of camerire’s age estimation method among Malay children - Sabqi, Aiman; Muhamed, Faiz; Ko, Bo Bo; Sukmasari, Susi (IIUM, 2014)
Objectives: Although many methods of chronological age (CA) estimation have been developed, dental age (DA) from development of tooth was found less environmentally influenced. The radiographic assessment on tooth development is considered to be more reliable than other methods. The objective of this study was to evaluate the reliability of Cameriere’s method amongst Malay children. Materials and Methods: It was a cross sectional study in which 162 OPGs of Malay children (81 boys, and 81 girls) with age range from 2 to 14 years old were collected from data bank at Kulliyyah of dentistry IIUM Kuantan using Planmeca Romexis® software. Inclusion and exclusion criteria were applied. The evaluation was carried out on each of the OPGs. Firstly, measurement of seven left or right permanent mandibular teeth was carried out using Cameriere’s methods on the Adobe Photoshop CS3® to determine the DA. Secondly, CA was determined by subtracting date of the OPG was taken with the patient’s birth. Finally, the DA was compared with the CA of the patient to determine the percentage error to get mean accuracy. Results: The method yielded a mean prediction error (ME) of 0.54 years for boys and 0.51 years for girls. ME was found to be slightly underestimated by -0.30 years for boys -0.17 years for girls. Conclusion: Cameriere’s methods can be recommended for practical application in clinical and forensic dentistry among the Malay population. Key Word: Chronological Age, Dental Age, Cameriere’s method, Mean Prediction Error